STUDY OF IRONY AND ENUNCIATIVE POLYPHONY IN LITERARY DISCOURSE (ACCORDING TO OSWALD DUCROT) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article is about a foreign language in the training of foreign language specialists, and the activity of teaching translation should be interrelated. The article also discusses the methodology for teaching translation work in foreign language courses and industry depending on the cost of developing evaluation criteria; practical suggestions are given based on the research results.